From local to regional competitive advantage (The case of Nikita's Homestead in Olkhon island - Baikal) - Kamila Borsekova; Katarina Petrikova; Anna Vanova (European Regional Science Association (ERSA), 2014)
Paper deals with the issue of a competitive advantage on the local level, its specifics, factors and a process of its creation, exploitation and building by using unique empirical case study. Through the theoretical knowledge, empirical research results and case study we want to point out how building a competitive advantage on the local level influences the development of the region and building of a strong competitive advantage on the regional level. The main aim of the paper is to define the process of identification, creation, building and exploitation of the local competitive advantage based on internal resources and cooperation and its influence on building the strong regional competitive advantage. The aim of the paper is fulfilled through processing wide theoretical knowledge supported by own empirical research results and an attractive case study. In the first part of the paper the theoretical knowledge about competitive advantage on the local level is processed. There are several theoretical approaches to a competitive advantage. As two basic approaches can be considered a market-based approach to the competitive advantage and a competitive advantage based on resources. A compromise between these two approaches offers demand orientated approach based on marketing places principles. A theoretical part of the paper is supported by the results of own empirical research aimed on identification and exploitation a competitive advantage on the regional and local level, its factors and their importance. The second part of the paper is dedicated to the methodology and results of own empirical research. The empirical research was realized through questionnaire survey by the Delphi method with an expert group consisting of domestic and foreign experts dealing with the issue of competitiveness and a competitive advantage. The third part of the paper summarizes practical implications of theoretical knowledge and empirical research results on the example of creating unique local production system located on the island Olkhon in lake Baikal. A basis for this local competitive advantage creates an excellent location on the island Olkhon inside the Baikal lake near the sacred place for Buryats. This uniqueness together with experienced and skilled human resources, developing and building of cooperation with the local suppliers and great reputation among the travelers from all over the world create strong inimitable competitive advantage. Even this competitive advantage is on the local level; it develops positively the whole island and helps to create the strong regional competitive advantage. The empirical case study is based on own experience gained during the research stay in Siberian Russia. The end of the paper includes conclusions, recommendation and inspiration for a practical exploitation of knowledge and experience contained in the paper.
Keywords: 330; competitive advantage; internal resources; uniqueness; location; cooperation